Efficacy of Double versus Single Homologous Intrauterine Insemination in Mild Male Factor Infertility and Pregnancy Outcome: A Randomised Controlled Trial - M Roopa; Sharath Kumar; Leena Kamath; Voorkara Udayashree; Sahana N Naik (Journal of Clinical and Diagnostic Research)
Introduction: Intrauterine Insemination (IUI) is a cost-effective, minimally invasive, and widely accepted Assisted Reproductive Technology (ART) procedure used to treat infertility. Various factors contribute to infertility, which in turn affect the success rate of IUI. To further increase the total concentration of sperm delivered and the window of sperm exposure to the oocyte, performing IUIs on two consecutive days (double IUI) has been proposed to enhance pregnancy rates, especially in cases of oligospermia. Double IUI aims to address the challenge of synchronising ovulation and insemination. Aim: To assess the efficacy of double IUI compared to single insemination in cases of mild male factor infertility. Material and Methods: A randomised clinical study was conducted in the Department of Obstetrics and Gynaecology (OBG), Shri Dharmasthala Manjunatheshwara College of Medical Sciences and Hospital Fertility Centre, Sattur, Dharwad, Karnataka, India from July 2021 to January 2022 on 200 patients. All 200 patients underwent ovulation induction with a sequential regimen using Letrozole or Clomiphene citrate, alongside highly purified Human Menopausal Gonadotropin (75 IU). All women underwent follicular monitoring and received an ovulation trigger. The first group of patients underwent a single IUI 36 hours after the Human Chorionic Gonadotropin (hCG) injection. Patients in the second group, who underwent double IUI, received the first IUI at 24 hours and the second IUI 48 hours after the hCG injection. Serum beta hCG was measured 15 days after the IUI to confirm the occurrence of pregnancy. Results: There were a total of 42 pregnancies (21%). The pregnancy rate for the single IUI group was 20%, while for the double IUI group, it was 22%. There was no significant difference between the single IUI and double IUI groups regarding positive outcomes (Chi-square=0.1210, p=0.7280). Conclusion: Double IUI increases the total concentration and quality of sperm delivered and extends the window of sperm exposure to the oocyte. This additional procedure may translate to increased pregnancy rates. However, in present study, no significant difference was noted in the achieved pregnancy rates. Higher-quality studies with larger populations are required to formulate a hypothesis.